+0  
 
0
523
1
avatar


I have a question which asks "Verify that inverse g(x) = g(x)" with the fractions g(x)=(x+1)/(x-1)

 

I am drawing a blank is all I can think of is showing that they are inverse of each other which isn't what the question is asking for

 Sep 17, 2016
 #1
avatar+129840 
+5

It's asking you to show that g(x) is it's own inverse

 

Fof g(x), write  y   and we have

 

y = ( x + 1) /(x - 1)     the object is to first get a single x by itself......multiply both sides by  x - 1

 

y ( x - 1)   =  x + 1

 

yx - y = x + 1       rearrange as

 

xy - x = y + 1       factor out x on the left

 

x(y - 1)  = y + 1    divide both sides by y - 1

 

x = [ y + 1 ] / [ y - 1]       "exchange" x with y

 

y = [x + 1 ] / [x - 1]     and for y, write g-1(x)

 

g-1(x) =  [x + 1 ] / [x - 1]     notice that this is the same as g(x)

 

 

cool cool cool

 Sep 17, 2016

2 Online Users

avatar